Analysis Student’s Mathematical Connection Ability of Class XII MIPA SMA N 1 Ngawen on Statistical Material - Apriliyani, Mila Nurul; Kumawati, Siti; Oktaviani, Utari; Nugroho, Heny (Proceeding International Conference on Science and Engineering, 2020)
The material in mathematics relates to each other and also relates to daily life. Likewise with statistics is one of the materials on the subject of mathematics that also has a relationship with other sciences, and has been widely used in daily life. This research explains the ability of the mathematic connections of the grade XII students of MIPA SMA N 1 Ngawen on the statistical material. With the aim to know the student’s mathematic connection ability. The methods used are qualitative descriptive with research instruments in the form of tests and interviews. The research subject consists of 10 students with an analysis model on this research based on its mathematical connection indicators. From this research gained ability on the indicator linking between concepts on a mathematical material and indicators linking between mathematical concepts with daily life belonging to the high, and low category for indicators The mathematical concept with other sciences.